Penerapan Aplikasi E-Filing sebagai Upaya Peningkatan Kepatuhan Wajib Pajak Orang Pribadi dalam Menyampaikan SPT PPh Tahunan di Direktorat Jenderal Pajak Kantor Pusat Periode Tahun 2021 sampai dengan Tahun 2023 - NingTyas, Indriani Rahayu (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to determine the influence of the level of Annual Income Tax Tax Compliance of Individual Taxpayers with the e-Filing Application at the Directorate General of Taxes at the Head Office. This research refers to the Tax Compliance Level Ratio which is still low. The method used in this research is qualitative with data collection techniques using data obtained from internal parties. The result is that the level of Tax Compliance through the e-Filing Application at the Directorate General of Taxes at the Head Office is classified as very good, but there are still several obstacles in Taxpayer compliance at the Directorate General of Taxes with the implementation of the E-Filing application, namely the lack of taxpayer knowledge regarding tax modernization, not yet understanding regarding the obligations and compliance of taxpayers, especially new taxpayers, network problems which cause the data transfer process to the server to sometimes be hampered, there are taxpayers who do not understand the E-Filing application. Keywords: e-Filing, Tax Compliance, Directorate General of Taxes, Head Office